PERBANDINGAN KEKERASAN BAHAN GLASS IONOMER CEMENT YANG DIRENDAM ANTARA OBAT KUMUR BERALKOHOL DENGAN OBAT KUMUR BEBAS ALKOHOL - Farid Yuristiawan; Gunawan Gunawan; Detty Iryani (Andalas Dental Journal, 2016)
Glass ionomer cement is one of the filling material that often used on the field of dentistry because it is relatively less expensive and mostly available. It’s existence in the mouth makes it susceptible to any substance that comes into mouth one of them is mouthwash which is a solution that used for many purposes such as antiseptic, astrigent, to prevent caries and bad breath. The aim of this research is to know the comparison of surface hardness of glass ionomer cement which soaked in alcohol containing mouthwash and alcohol-free mouthwash. This research is a laboratoric experimental type study. Sampels made from GC FUJI IX GP EXTRA for as much as 30 sampels were made and then soaked in artificial saliva for the first 24 hours inside incubator which temperature and humidity were controlled. Sampels then divided into 3 groups. First group will be soaked in alcohol containing mouthwash, second group will be soaked alcohol-free mouthwash and control group will be soaked in artificial saliva for 6 hours inside incubator. Listerine is the mouthwash that was used on this research and surface hardness was examined using Vickers Hardness Tester. The result of this research shows mean value for surface hardness of the first group is 16.36 VHN, 24.04 VHN for second group, and 43.60 VHN for control group. The result one way ANOVA with post hoc Bonferroni comparing test show significant results p = 0.00. In Conclusion there are significant differences of surface hardness between each groups, which surface hardness of the first group is lower than the second group, and both surface hardness of the first and second group are lowered than control group (p = 0.00). Key words : Glass Ionomer Cement, Mouthwash, Surface Hardness